Effects of aquatic exercise therapy on lung function in patients with asthma: a systematic review and meta-analysis - Xiaofeng Cheng; Jinsong Luo; Xianhui Liao (Frontiers in Physiology, 2026)
Background Exercise is recommended as an adjunctive therapy for asthma, yet the effects of aquatic exercise on pulmonary function remain uncertain because findings from randomized controlled trials (RCTs) have been inconsistent. This systematic review and meta-analysis aimed to synthesize the current evidence regarding the effects of aquatic exercise on pulmonary function in patients with asthma. Methods This systematic review was conducted in accordance with the PRISMA 2020 statement. PubMed, Embase, Web of Science, Cochrane Library, and CINAHL were systematically searched from database inception to 4 July 2026. Randomized controlled trials comparing structured aquatic exercise with routine care, health education, or land-based exercise in patients with asthma were included. The primary outcomes were forced expiratory volume in one second (FEV 1 ), FEV 1 (% predicted). Secondary outcomes included FEV 1 /FVC (%), forced vital capacity (FVC), FVC (% predicted), peak expiratory flow (PEF), PEF (% predicted), and forced expiratory flow at 25–75% of FEF (FEF 2575 % predicted). Age-based subgroup analyses were performed for FEV 1 and PEF. Results Thirteen RCTs involving 391 participants, were included. Aquatic exercise significantly improved FEV 1 (MD = 0.21 L, 95% CI 0.02–0.41), PEF (MD = 0.51, 95% CI 0.12–0.91), FVC (% predicted) (MD = 12.31%, 95% CI 7.25–17.37), and FEF 2575 % predicted (MD = 10.75%, 95% CI 3.05–18.45). No significant improvements were observed for FEV 1 (% predicted), FEV 1 /FVC (%), FVC, or PEF (% predicted). Subgroup analyses demonstrated that the improvement in FEV 1 was significant in participants aged <18 years but not in adults, whereas PEF improved in both age groups. Conclusions Aquatic exercise improves several indicators of pulmonary function in patients with asthma, particularly absolute FEV 1 , PEF, FVC (% predicted), and FEF 2575 % predicted. Children and adolescents may derive greater benefits in FEV 1 than adults, suggesting that aquatic exercise represents a promising adjunctive pulmonary rehabilitation strategy, especially for younger individuals with asthma.